2006
DOI: 10.1002/nbm.1092
|View full text |Cite
|
Sign up to set email alerts
|

MRI assessment of cartilage ultrastructure

Abstract: In T 2 -weighted MRI images joint cartilage can appear laminated. The multilaminar appearance is visualized as zones of different intensity. This appearance is based on the dipolar interaction of water molecules within cartilage zones of different collageneous network structures. Therefore, the MR visualization of zones of anisotropic arrangement of the collagen fibers depends upon their orientation to the static magnetic field (magic-angle effect). The aim of this article is to demonstrate the potential of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(126 citation statements)
references
References 46 publications
4
122
0
Order By: Relevance
“…In contrast to the adult cartilage appearance on MRI, with three zones, up to seven zones of different intensity have already been observed in juvenile femoral cartilage on MRI in various species (Grunder, 2006;Grunder et al, 2000;Grunder et al, 1998;Nieminen et al, 2000;Nissi et al, 2006;Xia et al, 2003). Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to the adult cartilage appearance on MRI, with three zones, up to seven zones of different intensity have already been observed in juvenile femoral cartilage on MRI in various species (Grunder, 2006;Grunder et al, 2000;Grunder et al, 1998;Nieminen et al, 2000;Nissi et al, 2006;Xia et al, 2003). Fig.…”
Section: Discussionmentioning
confidence: 92%
“…These differences reflect site and joint maturational differences (Lecocq et al, 2008), also observed by others (Brama et al, 2000;Julkunen et al, 2010). Grunder (2006) postulates that the site-related variation of cartilage laminae on MRI is an adaptation of the collagenous network to the regional different "biochemical requirements". Variations in collagen network organisation are also observed in young animals at different sites within the joint (Hyttinen et al, 2009) and also between different articular surfaces (Julkunen et al, 2010).…”
Section: Wwwecmjournalorg C Cluzel Et Al Articular Cartilage Develmentioning
confidence: 99%
“…These patterns have been confi rmed using polarised light microscopy (Hughes et al, 2005;Julkunen et al, 2009;Rieppo et al, 2009) and -MRI (Alhadlaq et al, 2004;Gründer, 2006;Nissi et al, 2006;Seidel et al, 2005;Xia et al, 2003). None of these studies has investigated the development of the fi bre orientation within in vivo implanted tissue-engineered cartilage over time.…”
Section: Introductionmentioning
confidence: 89%
“…However, the use of such probes is limited to in vitro cultures and cannot be used in implants. A second and probably more versatile example is the use of other measure-ment systems such as MRI or ultrasound elastomicrography imaging to follow tissue development [99][100][101]. Although, these techniques may provide ample information of the development of matrix throughout the construct, it has obvious drawbacks related to usability and cost-effectiveness.…”
Section: Current and Future Developmentsmentioning
confidence: 99%